Do corporate lawyers matter? Evidence from patents - Andriosopoulos, Dimitris; Czarnowski, Pawel; Marshall, Andrew (Journal of Corporate Finance, 2023)
Patent attorneys are responsible for obtaining patents that bring the highest expected profits for their corporate clients. We investigate the role of patent attorney capability in determining the value of corporate patents. We find that a one standard deviation increase in legal expertise leads to a 0.04% rise in patents' market valuation and a 3% increase in citations. This finding holds irrespective of the number of patents obtained by patent attorneys to date (process experience). To establish causality, we exploit a novel shock: the opening of new regional patent offices in the US; and changes in a firm's patent attorney. Overall, we find that capable patent attorneys matter as they increase both the economic and technological value of corporate patents.